The Implications of the Ukrainian Crisis for Russian Security and Foreign Policy - Dr Fuad Mansur Ahmeid; Dr Alhussien Ahmed Eljero (Journal of Scientific and Human Dimensions, 2026)
This research aims to analyzes the impact of the Ukrainian crisis on Russia's national security system and foreign policy trends, by revealing the nature of the changes that the crisis has imposed on Russian strategic thinking and Russia's position in the international system. The study used the descriptive analytical approach to describe the developments of the crisis and track its security and political consequences, as well as the analytical comparative approach to compare Russian behavior patterns before and after the crisis. The study population consists of Russian security and diplomatic policies and practices during the Ukrainian crisis, without relying on a statistical sample, given the theoretical nature of the study. The analytical approach is based on the analysis of facts, documents and international interactions relevant to the subject.   The importance of the research lies in its contribution to providing an integrated reading that links the security and political dimensions of Russian behavior, thereby enriching the literature on international security studies and the behavior of major powers in the context of ongoing crises. The study reached a number of conclusions, the most important of which are that the Ukrainian crisis represented a fundamental turning point in the concept of Russian national security, leading to a shift in foreign policy towards more confrontational approaches with the West, while expanding engagement with non-Western international spaces. The study also recommended the adoption of comprehensive analytical approaches tomulti-dimensional approaches when studying Russian security, and to enhance foresight studies to understand the long-term effects of major international crises
Keywords: The Ukrainian crisis; Russian national security; Russian foreign policy; the international system.